Islamic Moderation Education in Hizbul Wathan Activities at Muhammadiyah Al-Mujahidin Gunungkidul Islamic Boarding School: A Review of Character Values Based on Q.S. Ibrahim Verse 24 - Abdul Azis; Eko Tuanto (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
Islamic moderation has become an essential principle for achieving social harmony and religious tolerance in modern society. The application of moderation values in Hizbul Wathan activities still needs to be further explored, especially regarding the understanding of Quranic verses that support moderate attitudes, such as in QS. Ibrahim verse 24. This research uses a qualitative method with a case study and library research approach. The library research approach is conducted to see how the character of Islamic moderation in QS Ibrahim verse 24. The purpose of this research is to understand the values of Islamic moderation in the Hizbul Wathan activities at Muhammadiyah Al-Mujahidin Islamic Boarding School in Gunungkidul, which can shape moderate character based on QS Ibrahim verse 24. The results of this research reveal that the Hizbul Wathan activities at Al-Mujahidin Islamic Boarding School in Gunungkidul are capable of instilling Islamic moderation education in line with the values of moderate character in QS Ibrahim verse 24. The value of